Dynamics of protein secretion during adipocyte differentiation. Issue 8 (15th June 2016) - Ojima, Koichi; Oe, Mika; Nakajima, Ikuyo; Muroya, Susumu; Nishimura, Takanori
Abstract : The major functions of adipocytes include both lipid storage and the production of secretory factors. However, the type of proteins released from mouse 3T3‐L1 cells during adipocyte differentiation remains poorly understood. We examined the dynamics of secreted proteins during adipocyte differentiation using mass spectrometry (MS) combined with an iTRAQ ® labeling method that enables the simultaneous analysis of relative protein expression levels. A total of 215 proteins were identified and quantified from approximately 10 000 MS/MS spectra. Of these, approximately 38% were categorized as secreted proteins based on gene ontology classification. Adipokine secretion levels were increased with the progression of differentiation. By contrast, levels of fibril collagen components, such as subunits of type I and III collagens, were decreased during differentiation. Basement membrane components attained their peak levels at day 4 when small lipid droplets accumulated in differentiated 3T3‐L1 cells. Simultaneously, peak levels of collagen microfibril components that comprise type V and VI collagen subunits were also observed. Our data demonstrated that extracellular matrix components were predominantly released during the early and middle stages of adipocyte differentiation, with a subsequent increase in the secretion of adipokines. This suggests that 3T3‐L1 cells secrete adipokines after their ECM is constructed during adipocyte differentiation. Abstract : Adipocytes are increasingly recognized as secreting cells. Here, we characterized secreted proteins during adipocyte differentiation using a quantitative proteomic approach. Adipocytes predominantly secreted extracellular matrix components during the early and middle stages of differentiation. Adipokines were gradually released as adipocyte differentiation proceeded. Our proteomic profiling revealed that distinct factors are released at different stages of adipocyte differentiation.